2019
DOI: 10.1055/s-0039-1688512
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Open Reduction and Internal Fixation of Bilateral Fractures of the Distal Radius

Abstract: Background Bilateral distal radius fracture (DRF) is an uncommon injury. We described the outcomes of 10 consecutive cases of bilateral DRF treated with open reduction and internal fixation (ORIF) at our institution. Materials and Methods We retrospectively searched our electronic medical records data for all patients 18 years of age or older treated surgically for bilateral DRF over a 6-year period (2011–2016). Patient demographics, fracture classification, fixation method, postoperative complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…A recent retrospective study of 10 bilateral radius fractures treated with open reduction and internal fixation showed complications in one-half of the patients after a mean 2.4-year follow-up. 36 As there are no standardized and evidence-based protocols for the treatment of complex bilateral upper extremity injuries, a question remains whether something could have been done differently. Both distal radial fractures could have been treated with open reduction and internal fixation using plates and screws, but our idea was to use minimally invasive methods to yield the best result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective study of 10 bilateral radius fractures treated with open reduction and internal fixation showed complications in one-half of the patients after a mean 2.4-year follow-up. 36 As there are no standardized and evidence-based protocols for the treatment of complex bilateral upper extremity injuries, a question remains whether something could have been done differently. Both distal radial fractures could have been treated with open reduction and internal fixation using plates and screws, but our idea was to use minimally invasive methods to yield the best result.…”
Section: Discussionmentioning
confidence: 99%
“…For the open or highly comminuted fractures, external fixation can be used. A recent retrospective study of 10 bilateral radius fractures treated with open reduction and internal fixation showed complications in one‐half of the patients after a mean 2.4‐year follow‐up 36 …”
Section: Discussionmentioning
confidence: 99%
“…Bilateral DRFs are exceedingly rare compared to unilateral DRFs. [12] While 87% of unilateral DRFs are treated conservatively, [3] ORIF is the most widely adopted surgical treatment. [13] No specific treatment has been described for bilateral DRFs in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Williksen et al [14] used both the Q-DASH and the MAYO scores; however, some surgeons used only Q-DASH scores. [4,[11][12][13] In a meta-analysis, Wang et al [15] reported that higher DASH scores were observed with ORIF, compared to EF. In contrast, one year later, in the meta-analysis of Lee et al, [16] there was no significant difference between the ORIF and EF groups in terms of the Q-DASH scores.…”
Section: Discussionmentioning
confidence: 99%
“…Distal radius fracture is one of the most common orthopedic injuries treated by orthopedic surgeons, however, simultaneous bilateral distal radius fracture in the adult population is a relatively rare injury. 1 , 2 , 3 To the best of our knowledge, bilateral distal radius fracture associated with pregnancy during the lockdown period of COVID 19 is not only the challenging injury pattern but also un-reported in the literature to date. However, there are very few studies reporting bilateral distal radius fractures during pregnancy.…”
Section: Introductionmentioning
confidence: 99%